2007
DOI: 10.1016/j.brainresrev.2007.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine reward circuitry: Two projection systems from the ventral midbrain to the nucleus accumbens–olfactory tubercle complex

Abstract: Anatomical and functional refinements of the meso-limbic dopamine system of the rat are discussed. Present experiments suggest that dopaminergic neurons localized in the posteromedial ventral tegmental area (VTA) and central linear nucleus raphe selectively project to the ventromedial striatum (medial olfactory tubercle and medial nucleus accumbens shell), whereas the anteromedial VTA has few if any projections to the ventral striatum, and the lateral VTA largely projects to the ventrolateral striatum (accumbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

83
1,281
11
39

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,272 publications
(1,429 citation statements)
references
References 370 publications
83
1,281
11
39
Order By: Relevance
“…In response to the successive exposures to a rewarding stimulus, the role of the VTA dopamine system is rather sophisticated: the Acb dopamine signaling increases after the first exposure and then habituates with the repeated exposures and becomes a predictive signal of the stimulus (Salamone and Correa, 2012;Schultz, 2010). On top of this functional complexity, the VTA dopamine neurons are located in diverse sub-regions within this nucleus that, in turn, are part of different neuronal circuits for which their independent physiological role is virtually unknown (Ferreira et al, 2008;Ikemoto, 2007Lammel et al, 2011. Here, we found that IF and PBP dopamine neurons are activated in mice exposed to either one or four HFD consumption events; however, the level of activation was higher in mice exposed to four HFD consumption events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the successive exposures to a rewarding stimulus, the role of the VTA dopamine system is rather sophisticated: the Acb dopamine signaling increases after the first exposure and then habituates with the repeated exposures and becomes a predictive signal of the stimulus (Salamone and Correa, 2012;Schultz, 2010). On top of this functional complexity, the VTA dopamine neurons are located in diverse sub-regions within this nucleus that, in turn, are part of different neuronal circuits for which their independent physiological role is virtually unknown (Ferreira et al, 2008;Ikemoto, 2007Lammel et al, 2011. Here, we found that IF and PBP dopamine neurons are activated in mice exposed to either one or four HFD consumption events; however, the level of activation was higher in mice exposed to four HFD consumption events.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative analysis was performed in sections between bregma 0.86 and 1.18 mm for the Acb, between bregma −1.22 and −1.94 mm for the lateral hypothalamic area (LHA), and between bregma −3.28 and −3.92 mm for the VTA. For the analysis, the Acb was subdivided into medial Acb shell (MAcbSh), lateral Acb shell (LAcbSh) and Acb core (AcbC) while the VTA was subdivided into paranigral (PN), parabrachial pigmented (PBP) and interfascicular (IF) subnuclei, according to previous descriptions (Ikemoto, 2007;Kelley, 2004). Anatomical limits of each brain region were identified using a mouse brain atlas (Paxinos and Franklin, 2001).…”
Section: Quantitative Neuroanatomical Analysismentioning
confidence: 99%
“…The nucleus accumbens is considered as an important region of brain reward circuits (Basar et al, 2010; Carlezon & Thomas, 2009; Day & Carelli, 2007; Floresco, 2015; Ikemoto, 2007; Salamone, Correa, Mingote, & Weber, 2005). Spiny GABAergic neurons in the nucleus accumbens are involved in major depression (Francis & Lobo, 2016; Lim, Huang, Grueter, Rothwell, & Malenka, 2012; Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The mesocorticolimbic dopaminergic system, composed of dopaminergic neurons and their projections, has been proven to be involved in the reward‐motivated behaviors of individuals (Cohen, Haesler, Vong, Lowell, & Uchida, 2012; Ikemoto, 2007). The dopaminergic neurons are mainly located in the ventral tegmental area (VTA) (Beckstead, Domesick, & Nauta,1979) and project primarily to the prefrontal cortex (PFC), olfactory tubercle (OT), nucleus accumbens (NAc), dorsal striatum (ST), and the amygdala (AMy).…”
Section: Introductionmentioning
confidence: 99%